The Analysis of Urban Form Elements Effect on the Behaviour of the travel and to Develop low-carbon City Case Study: Tabriz Metropolitan - rasoul ghorbani; Akbar Asghari Zamani; rahim gholamhosseini (تحقیقات کاربردی علوم جغرافیایی)
There is a wide body of literature indicating a strong link between urban form and carbon emissions in the transport sector, this is done through the impact of city form components on citizen’s travel behavior. Therefore, in urban low carbon development theory, the reduction of cavalry production through changes in urban form elements is considered. This paper investigates the effects of urban form components on Tabriz Metropolitan travel behavior. Tabriz’s single-engine city form makes maximum use of personal cars for city trips resulting in increased carbon emissions in Tabriz’s urban air. Therefore, the impact of urban form elements on car-driven travel behavior has been selected as the most fundamental pillar of low carbon studies in Tabriz. The results of   the   application   of the Moran method show that the criteria used are mainly clustered and therefore have spatial autocorrelation and it is very useful to use location- based regression methods such as geographic weight regression. The results of this method show that access to metro stations in Tabriz metropolitan area the coefficient of importance of 0/40 have the least relationship with urban travel behavior, respectively and the two factors combining urban land use and business center access with a factor of importance of 0/54 are most important in urban travel behavior. It was therefore concluded that the components of urban form are more important in urban travel behavior and it needs to get more attention form city managers and planners in shaping a low-carbon city.